Syndecan‐1 identifies and controls the frequency of IL‐17‐producing naïve natural killer T (NKT17) cells in mice. Issue 11 (10th September 2015) - Dai, Hong; Rahman, Ayesha; Saxena, Ankit; Jaiswal, Anil K; Mohamood, Abdiaziz; Ramirez, Lourdes; Noel, Sanjeev; Rabb, Hamid; Jie, Chunfa; Hamad, Abdel Rahim A
Abstract : Invariant natural killer T ( i NKT) cells recognize glycolipids as antigens and diversify into NKT1 (IFN‐γ), NKT2 (IL‐4), and NKT17 (IL‐17) functional subsets while developing in the thymus. Mechanisms that govern the balance between these functional subsets are poorly understood due, partly, to the lack of distinguishing surface markers. Here we identify the heparan sulfate proteoglycan syndecan‐1 (sdc1) as a specific marker of naïve thymic NKT17 cells in mice and show that sdc1 deficiency significantly increases thymic NKT17 cells at the expense of NKT1 cells, leading to impaired i NKT cell‐derived IFN‐γ, both in vitro and in vivo. Using surface expression of sdc1 to identify NKT17 cells, we confirm differential tissue localization and interstrain variability of NKT17 cells, and reveal that NKT17 cells express high levels of TCR‐β, preferentially use Vβ8, and are more highly sensitive to ɑ‐GalCer than to CD3/CD28 stimulation. These findings provide a novel, noninvasive, simple method for identification, and viable sorting of naïve NKT17 cells from unmanipulated mice, and suggest that sdc1 expression negatively regulates homeostasis in i NKT cells. In addition, these findings lay the groundwork for investigating the mechanisms by which sdc1 regulates NKT17 cells.